Analysis of Literacy Programs in Increasing Students' Reading Interest in Schools - Asih Tri Lestari; Didan Faisal; Dinda Adila Aprina; Rahma Fauziah Azzahra; Irpan Taupik (Socrates: Journal of Education, Philosophy and Psychology, 2024)
School libraries play a crucial role in supporting the learning process and developing students' literacy. As information centers, they provide a diverse range of reading materials and enhance understanding and critical thinking skills. Literacy encompasses reading, writing, and comprehension abilities that are essential in education. Well-implemented literacy programs strengthen students' skills in accessing, analyzing, and utilizing information across various contexts. Students' reading interest is a key factor in the success of these programs and can be fostered through engaging literacy activities with support from families and schools. The involvement of stakeholders such as government bodies, educational institutions, and communities is vital for creating an environment that encourages reading habits. With effective library management and collaboration among all parties involved, literacy programs can positively impact educational quality and prepare students to face global challenges.